If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+8=6x-26
We move all terms to the left:
2x+8-(6x-26)=0
We get rid of parentheses
2x-6x+26+8=0
We add all the numbers together, and all the variables
-4x+34=0
We move all terms containing x to the left, all other terms to the right
-4x=-34
x=-34/-4
x=8+1/2
| 2(2x+3)-15x=2x-7 | | (t+7)=32 | | 5x-5.52=-4.32 | | m=4m+9 | | 0.5/x=20 | | -5(3x-7)+11=x | | 6w=45-4w | | 2^x+7=5/4 | | 3/2x-5=2/x-4 | | 3x-5.42=-3.89 | | -4(2+x)=56 | | 2(6z+)=28 | | 2x-12=6x+24 | | 2x+8-7x-2=3x+14 | | 3(4-x)=-27 | | -2+3x=6x+4 | | 6x–11=7 | | 3k^2-13k+10=0 | | 6x–11=7 | | x^2=2.89^3 | | X+6=2-2x | | 3k^2-13k+-10=0 | | −4(2+x)=56 | | (9x+7)+(-3x+20)=39 | | H(x+2)=(x+2)^2-2(x+2) | | 5a+2 =a | | m÷3.5=16 | | –2x=–18 | | 1=w/2+7 | | -8(x+9)+2=7x-27 | | 575=23(x+16) | | 3(5x+5)=-39+9 |